One nation divisible : class, race and ethnicity in the United States since 1938. - Polenberg, Richard (Harmondsworth : Penguin Books, 1980)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: geschiedenis; Verenigde Staten